Diseño de protocolo para la conversión de vehículo con motor de combustión interna a motor eléctrico. - Torres Chaparro, Cristian Camilo (Universidad Antonio Nariño, 2022)
Electric vehicles are increasingly crucial in the energy transition in the transport sector and the reduction of pollutants. This project shows the transformation process from a conventional vehicle with an internal combustion engine to one with an electric motor. The objective is to incentivize the insertion of electric vehicles in Duitama city's taxi fleet.